Redesain Museum Situs Purbakala Patiayam Di KudusPendekatan pada Konsep Arsitektur Metafora - Hefi Ristiawan, Ari; , Dr. Ir. W. Nurjayanti. MT; , Ronim Azizah, ST. MT (2016)
Situs Patiayam is one of the sites that contain fossils in Indonesia and Museum Patiayam is part of Situs Patiayam. This museum has many collections of objects, relics or traces of past civilization, including artifacts, fossils. Museum is one of public facilities which can be visited for education and recreation purposes to see the collections of museum, including physical and data collection, which are one of the main considerations. A museum has to be managed professionally with a well-display of the collections to be able to survive and developed. Redesign of the Museum Archeological SitusPatiayam is an attempt to improve the services to the public and visitors. It is done by conservation, management, maintenance, protection, and provides systematically and conceptually display of the objects which have high values or cultural heritage. The process of redesign includes improvement of layout and room designs, interior and exterior architectural appearance as well as its structure and utilities. The concept of planning and design of Museum Archeological Situs Patiayam include analysis of site, access, view, noise, climatology, orientation, landscape, building configuration, interior and exterior view, structures and utilities. Results of the analysis lead to metaphors approach for the physical appearance. The metaphor takes the shape of shells fossils for the main building of the Archaeological Museum Situs Patiayam new design.